Toward Evidenced-Based Assessment and Treatment of Pediatric Psychogenic Nonepileptic Seizures - Psihogios, Alexandra M.; Drossos, Tina; Afzal, Khalid I. (Journal of Pediatric Epilepsy, 2017)
Objective Psychogenic nonepileptic seizures are common among children and adolescents, but evidenced-based assessment and treatment guidelines are lacking. This review aimed to evaluate the current status of the pediatric literature on psychogenic nonepileptic seizures (PNES).Method A review of the relevant pediatric literature was performed. A case example was constructed to further elucidate assessment and treatment of pediatric PNES in a clinical context.Results The most common manifestation of PNES in children and adolescents is motionless unresponsiveness. Youth typically experience psychological dysfunction, including somatization, history of trauma, depression, anxiety, and school problems. Simultaneous video and 24-hour electroencephalogram recordings are gold standards of PNES assessment, but neuropsychological evaluation offers an additional tool for diagnosing PNES. Rigorous research on the effectiveness of psychotherapy for pediatric PNES patients is lacking.Conclusion In addition to electrophysiological characteristics, there are several core clinical features that distinguish epileptic from nonepileptic events, including higher rates of somatization among youth with PNES. Psychoeducation combined with cognitive behavioral therapy and the use of selective serotonin reuptake inhibitors may be beneficial for reducing symptom burden.
Keywords: psychogenic; nonepileptic; seizures; pediatric; pseudoseizures